(untitled) (International Journal on Stereo & Immersive Media, 2025)
This article aims to clarify early astronomer-photographers’ creative and intriguing techniques for capturing stereoscopic images of celestial bodies during the 19th and early 20th centuries. We will showcase these astronomical stereoscopic photos in chronological order, based on when the first images of each astronomical object were taken. Additionally, we will outline the fundamental processes involved in achieving the stereoscopic effect for each subject. The article introduces some very rare stereoscopic images of the Moon on glass positives kept at the FBS Foundation in Spain.